The everlasting [large type] - Harrow, Alix E. (Thorndike Press large print high octane., 2025)
"Sir Una Everlasting was Dominion's greatest hero: the orphaned girl who became a knight, who died for queen and country. Her legend lives on in songs and stories, in children's books and recruiting posters--but her life as it truly happened has been forgotten. Centuries later, Owen Mallory--failed soldier, struggling scholar--falls in love with the tale of Una Everlasting. Her story takes him to war and then into the past itself. Una and Owen are tangled together in time, bound to retell the same story over and over again, no matter what it costs. But that story always ends the same way. If they want to rewrite Una's legend, they'll have to rewrite history itself"--